Hybrids Obtained Through Ecological-Geographical Long-Term Hybrids - Хайдаров М. Р. (Web of Journals Publishing, 2023)
This article discusses various approaches to the concept of semantic field in linguistics.
Keywords: lexical field, connotation, concept, hyperonym, hyponym.